The tumour suppressor gene l(2)giant discs is required to restrict the activity of Notch to the dorsoventral boundary during Drosophila wing development. - Klein, T. (Developmental Biology, 2003)
During the development of the Drosophila wing, the activity of the Notch signalling pathway is required to establish and maintain the organizing activity at the dorsoventral boundary (D/V boundary). At early stages, the activity of the pathway is restricted to a small stripe straddling the D/V boundary, and the establishment of this activity domain requires the secreted molecule fringe (fng). The activity domain will be established symmetrically at each side of the boundary of Fng-expressing and non-expressing cells. Here, I present evidence that the Drosophila tumour-suppressor gene lethal (2) gaint discs (lgd) is required to restrict the activity of Notch to the D/V boundary. In the absence of lgd function, the activity of Notch expands from its initial domain at the D/V boundary. This expansion requires the presence of at least one of the Notch ligands, which can activate Notch more efficiently in the mutants. The results further suggest that Lgd appears to act as a general repressor of Notch activity, because it also affects vein, eye, and bristle development.